2015
DOI: 10.1002/chir.22559
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Chiral Separation of Flavanone, Naringenin, and Hesperetin Enantiomers by RP‐UHPLC‐DAD

Abstract: A rapid and effective RP-UHPLC-DAD method for enantioseparation of three flavanones, i.e., flavanone, naringenin, and hesperetin, was developed and validated. Chromatographic separation of the analytes was performed using a Chiralpak AD-3R analytical column under reverse phase conditions with methanol as the mobile phase. The method was validated in the concentration range of 0.2 to 50 µg/mL for enantiomers of flavanone and 0.5 to 50 µg/mL for enantiomers of naringenin and hesperetin. The limits of quantificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Commercial preparation of racemic flavanone contains ( 2R )- and ( 2S )-enantiomers (Si-Ahmed et al, 2010; Baranowska et al, 2016). Studies of the molecular interaction of these flavanone enantiomers with the active sites of CYP2A6.1 indicated that the C2´ atom of the ( 2R )-isomer was located nearer (distance 3.8Å) the iron center of CYP2A6 (2FDY) as compared with the ( 2S )-isomer (distance 6.9Å), while C6 of ( 2S )-flavanone was more closely located to the iron center of CYP2A6 than that of (2R)-isomer (Figure 11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Commercial preparation of racemic flavanone contains ( 2R )- and ( 2S )-enantiomers (Si-Ahmed et al, 2010; Baranowska et al, 2016). Studies of the molecular interaction of these flavanone enantiomers with the active sites of CYP2A6.1 indicated that the C2´ atom of the ( 2R )-isomer was located nearer (distance 3.8Å) the iron center of CYP2A6 (2FDY) as compared with the ( 2S )-isomer (distance 6.9Å), while C6 of ( 2S )-flavanone was more closely located to the iron center of CYP2A6 than that of (2R)-isomer (Figure 11).…”
Section: Discussionmentioning
confidence: 99%
“…Flavanone [a racemic mixture of ( 2R )- and ( 2S )-enantiomers] (Akashi et al, 1998; Si-Ahmed et al, 2010; Baranowska et al, 2016), flavone, 5-, 6-, and 7-hydroxyflavone (5OHF, 6OHF, and 7OHF), 5,7- and 7,8-dihydroxyflavone (57diOHF and 78diOHF), 5-, 6- and 7-hydroxyflavanone (5OHFva, 6OHFva and 7OHFva), α -naphthoflavone (ANF), coumarin, and N , N ´, N ´´-triethylenethiophosphoramide (thio-TEPA) were obtained from Sigma-Aldrich (St. Louis, MO, USA) and Wako Pure Chemicals (Osaka, Japan). 2´-, 3´-, and 4´-Hydroxyflavanone (2´OHFva, 3´OHFva, and 4´OHFva) were purchased from Tokyo Kasei Co. (Tokyo).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We required an easy, less time consuming, sensitive, robust, as well as highly reproducible bioanalytical method for the quantification NRG in the brain and blood samples as per the evaluation of pharmacokinetic parameters. There are so many analytical methods are reported for the quantification of NRG but not a single bioanalytical method reported for brain or brain homogenate samples for the brain-PK including for the quantification of NRG as single analyte with high robust method (Sun et al, 2014, Wang et al, 2014, Magiera et al, 2012, Baranowska et al, 2016a, Baranowska et al, 2016b). The most important parameter for the estimation of NRG-bioanalytical method (upto nanogram i.e.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been many reports on CSPs such as polysaccharides, 21–23 macrocycles (crown ether, 24 cyclodextrins, 25,26 and calixarene 27 ) and other types of CSPs. 28 However, there are still some limitations for macrocyclic stationary phases including limited chiral sites, irregular structures, or poor separation effects.…”
mentioning
confidence: 99%